2018
DOI: 10.3390/s18020641
|View full text |Cite
|
Sign up to set email alerts
|

Experimental L-Band Airborne SAR for Oil Spill Response at Sea and in Coastal Waters

Abstract: Satellite synthetic aperture radar (SAR) is frequently used during oil spill response efforts to identify oil slick extent, but suffers from the major disadvantages of potential long latency between when a spill occurs and when a satellite can image the site and an inability to continuously track the spill as it develops. We show using data acquired with the Uninhabited Aerial Vehicle SAR (UAVSAR) instrument how a low noise, high resolution, L-band SAR could be used for oil spill response, with specific exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Previous research [2,5,7] indicated a relationship between the oil slick thickness and the damping effect on the sea surface roughness. Thicker layers cause more damping of the capillary and gravity-capillary waves, and hence appear darker than thinner layers of oil in SAR imagery.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous research [2,5,7] indicated a relationship between the oil slick thickness and the damping effect on the sea surface roughness. Thicker layers cause more damping of the capillary and gravity-capillary waves, and hence appear darker than thinner layers of oil in SAR imagery.…”
Section: Introductionmentioning
confidence: 99%
“…During emergency response, the oil containment and recovery are the main cleanup operations with potential to minimize these impacts. The thickness of the oil slick has a significant effect on the recovery efficiency rates, being higher over the thicker layers [1,2]. Synthetic Aperture Radars (SAR) data are most frequently used by operational oil spill surveillance service providers to detect and monitor oil slicks on the sea surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shortcoming of satellite-borne remote sensing is that it cannot monitor spills in real-time. With the rapid development of unmanned aerial vehicles (UAV), airborne radar detection technology has progressed quickly [15][16][17]. However, UAVs require favorable weather.…”
Section: Introductionmentioning
confidence: 99%